2016
DOI: 10.4238/gmr.15027423
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of QTLs for panicle exsertion and its relationship with yield and yield-related traits in rice (Oryza sativa L.)

Abstract: ABSTRACT. Panicle exsertion (PE) is an important morphological trait that is closely associated with spikelet fertility and grain yield. To understand the genetic basis of PE and its relationships with yield and yield-related traits, a recombinant inbred population consisting of 240 lines derived from a cross between an Indica cultivar 'Kasalath' and a Japonica germplasm 'TD70', was studied over two years. PE was significantly correlated with plant height, heading date (HD), panicle length (PL), and panicle ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Similar results were also reported by Shishir Sharma et al [44] and [48,49]. Current study reveals that DFF had a highly significantly negative correlation with CPE, which was similar to the results reported by [39,21,22]. However, in this current study we found that DFF had significantly negative correlation with PH, TGW, FLL and FLW.…”
Section: Correlation Data Between Agro-morphological Charac-ters Of Csupporting
confidence: 92%
See 3 more Smart Citations
“…Similar results were also reported by Shishir Sharma et al [44] and [48,49]. Current study reveals that DFF had a highly significantly negative correlation with CPE, which was similar to the results reported by [39,21,22]. However, in this current study we found that DFF had significantly negative correlation with PH, TGW, FLL and FLW.…”
Section: Correlation Data Between Agro-morphological Charac-ters Of Csupporting
confidence: 92%
“…58, before and after planting, respectively and, at ICRISAT Patancheru Hyderabad. Complete panicle emergence in mutants was measured at the time of maturity from the base of panicle to the tip of the last spikelet Zhan, Chengfang et al [21] and Zhao, C. F. et al [22]. The mutant lines panicle internodes were emerged completely from the flag leaf.…”
Section: Identification Of Mutants Having Complete Panicle Emergence mentioning
confidence: 99%
See 2 more Smart Citations
“…The panicle traits are the most intuitive and representative rice plant part that is utilized in determining its identity and genetic diversity, as well as in estimating rice yield and quality (Chen et al 2001;Ma et al 2006;Wu et al 2016). Therefore, the characterization of rice panicle traits in relation to agricultural production and genetic diversity has long been an important research topic (Zhou et al 2003;Wang et al 2007;Zhou et al 2014;Zhao et al 2016;Adriani et al 2016). As the study of genetic diversity of morphological traits can directly provide information on germplasm richness and provide important information for farmers or breeders especially when the resource population is large, using morphological traits to study genetic diversity is considered as a very simple and economical approach.…”
Section: Introductionmentioning
confidence: 99%